RESEARCH OF THE MOVEMENT STRUCTURE OF THE QUALIFIED WEIGHTLIFTERS IN THE SNATCH AND THE CLEAN AND JERK TAKING INTO ACCOUNT MODELLING OF BIOMECHANICAL COMPONENTS - Oļeško, Valentin; Ivanov, Artjom; Čupriks, Leonīds; Čuprika, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The research was conducted during the training process of Ukrainian, Russian and Latvian weightlifters and their participation in international competitions (the World and European Championships). The aim of the current study was to identify qualified weightlifters movements development regularities snatch and clean and jerk through the biomechanical component modelling. A total of 442 qualified weightlifters participated in the research: 242 male weightlifters and 200 female weightlifters. All athletes were divided into three groups according to their weight category: male weightlifters: Іst group – 56–69 kg; ІІnd group – 77–94 kg; ІІІrd group – 105 and +105 kg; female weightlifters: Іst group – 48-58 kg; ІІnd group – 63-69 kg; ІІІrd group – 75 and +75 kg. Obtaining the biomechanical parameters of technical training of the qualified weightlifters in the snatch and the clean and jerk during the competitions, biodynamic and biokinematic complex of movement parameters of the interaction between the athletes and the barbell was examined using the electro-optical complex „Weightlifting analyzer 3.0“,produced in Germany. In all weight categories in the final acceleration phase (F3FAP) and supported squat phase (F4SSP) the best efforts in the snatch are made by female weightlifters, although they lift considerably less weight of loads (by 15–25 %) than male weightlifters. In the first group of weight categories the parameters differ by 1,4 and 4,2 % (р ≤ 0,005), in the second group of weight categories – by 8,9 and 3,9 % (р ≤ 0,005), however in the third group of weight categories differences were only observed in the final acceleration phase (F3 FAP) – by 3,7 % (р ≤ 0,005). The results of the research show that in the instant of the first application of the maximum force (v F1) females develop higher speed of the barbell than males (by 44,0 %). The same tendency is observed in the instant of the maximum knee extension (v MAХ KE) – in this phase the vertical speed of the barbell among female weightlifters is by 4,5 % (р ≤ 0,05) higher than among male weightlifters. Females of the Ist and the IIIrd group of weight categories achieve the best results in the final acceleration phase (v MAX) – they are by 6,8 and 5,4 % (р ≤ 0,05) higher than the same parameters of males of the Ist and the IInd group of weight categories. Significant differences have been also observed in biomechanical parameters of the barbell's movement among representatives of different genders and weight categories. Moreover, in the Ist group of weight categories differences mainly exist in the preliminary squat phase (h PR.SQ.), when female parameters are by 4,5 % higher than male parameters; in the instant of the attainment of the maximum height of the barbells' displacement (h MAX) they are by 7,5 % higher respectively; the amount of force in the process of interaction between the athletes and the barbell in the active braking phase (FАBP) is by 5,3 % bigger respectively. In the IInd group essential differences appeared in the vertical displacement of the barbell in the instant of the attainment of the maximum height (h MAX), female parameters are by 7,3 % higher than male parameters; in the supported squat phase (h SQUAT.) the opposite tendency can be observed as parameters among males are by 47,8 % higher than female parameters; the amount of force applied to the barbell in the supported squat phase (FSSP) among females are by 3,4 % higher than among males. In the IIIrd group significant differences are noticed in the vertical displacement of the barbell in the instant of the attainment of the maximum height (h MAX), female parameters are by 6,5 % better than male parameters; the amount of force in the process of interaction between the athletes and the barbell in the active braking phase (F ABP) among females is by 5,7 % higher than among males.Thus biomechanical parameter changes of the execution technique of competitive exercises in the clean and jerk among the weightlifters of different gender and weight categories show more than 62,5 % of differences in respect of biodynamic and biokinematic (speed and spatial) parameters of support interaction of the athletes. In spite of the same phase structure of the exercises, movements of the first method of the clean and jerk considerably differ from the similar parameters of the snatch technique. This indicates individualisation of model parameter formation of technical training of the qualified athletes, performing competitive exercises within the certain group of weight categories, taking into consideration gender differences.